1997
DOI: 10.1590/s0100-879x1997000600007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of discocyte frequency and ATP concentration in preserved blood: A morphological indicator of red blood cell viability

Abstract: Red blood cells (RBC) are viable if kept in an adequate preservative solution, although gradual changes in morphology and metabolism may occur. There is a gradual decrease in adenosine-5'-triphosphate (ATP) concentration, pH, glucose consumption, and enzyme activity during preservation. The normal discocyte shapes are initially replaced by echinocytes and stomatocytes and, at final stages, by spherocytes, the last step before splenic sequestration. Post-transfusional survival has been correlated with the ATP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
3
Order By: Relevance
“…O fato de ATP e 2,3 BPG se exaurirem em poucas semanas em UTE, em condições usuais, tem levado ao desenvolvimento de novas soluções aditivas que mantêm a viabilidade e a funcionalidade dos eritrócitos por tempos maiores. 22,23 As determinações de ATP e 2,3 BPG baseiam-se em técnicas enzimáticas reprodutíveis e bem estabelecidas, 24 mas não constam da RDC n° 153/2004 7 e não são realizadas rotineiramente no acompanhamento de UTE em nosso país, possivelmente por não serem comportadas pelos recursos e infraestrutura disponíveis nos hemocentros e bancos de sangue. A porcentagem de discócitos nas UTE é obtida a partir da contagem diferencial das formas eritrocitárias feita após uma simples diluição em líquido para contagem de eritrócitos, ao microscópio de luz.…”
Section: Discussionunclassified
“…O fato de ATP e 2,3 BPG se exaurirem em poucas semanas em UTE, em condições usuais, tem levado ao desenvolvimento de novas soluções aditivas que mantêm a viabilidade e a funcionalidade dos eritrócitos por tempos maiores. 22,23 As determinações de ATP e 2,3 BPG baseiam-se em técnicas enzimáticas reprodutíveis e bem estabelecidas, 24 mas não constam da RDC n° 153/2004 7 e não são realizadas rotineiramente no acompanhamento de UTE em nosso país, possivelmente por não serem comportadas pelos recursos e infraestrutura disponíveis nos hemocentros e bancos de sangue. A porcentagem de discócitos nas UTE é obtida a partir da contagem diferencial das formas eritrocitárias feita após uma simples diluição em líquido para contagem de eritrócitos, ao microscópio de luz.…”
Section: Discussionunclassified
“…Several physical and chemical factors have been implicated in the development of echinocytes. These include the contrast agents used in radiology [3], X-rays and electric pulses [7] and the length of time that blood is stored [4,5]. Evidence suggests that there is a relationship between the ATP-Mg 2+ complex and the occurrence of echinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that there is a relationship between the ATP-Mg 2+ complex and the occurrence of echinocytes. Some authors have proposed us-ing the proportion of echinocytes in the blood as an indicator of an insufficient level of ATP in the erythrocytes [4,9]. Other authors, however, have not confirmed this relationship [5,8].…”
Section: Discussionmentioning
confidence: 99%
“…Durante o período de estoque para transfusão, há consumo de glicose, acúmulo de íons potássio no meio extracelular e queda dos níveis de ATP que correlacionam com alterações morfológicas e com a sobrevida pós-transfusional, além de uma lenta diminuição de atividades enzimáticas, com perda de fosfolipídeos e oxidação das proteínas e dos lipídeos da membrana. 3,[13][14][15][16][17] As soluções mais empregadas, rotineiramente, são SAGM e ADSOL, as quais mantêm os eritrócitos…”
unclassified